PLGA-Based Drug Delivery Systems for Remotely Triggered Cancer Therapeutic and Diagnostic Applications - Shen, Xue; Li, Tingting; Xie, Xiaoxue; Feng, Yi; Chen, Zhongyuan; Yang, Hong; Wu, Chunhui; Deng, Shengqi; Liu, Yiyao (Frontiers in Bioengineering and Biotechnology, 2020)
Intelligent drug delivery systems based on nanotechnology have been widely developed and investigated in the field of nanomedicine since they were able to maximize the therapeutic efficacy and minimize the undesirable adverse effects. Among a variety of organic or inorganic nanomaterials available to fabricate drug delivery systems for cancer therapy and diagnosis, poly(D,L-lactic-co-glycolic acid) (PLGA) has been extensively employed due to its biocompatibility and biodegradability. In this paper, we review the recent status of research on the application of PLGA-based drug delivery systems (DDSs) in remotely triggered cancer therapy and tumor diagnosis. We discuss the targeting strategies which provide PLGA-based DDSs with passive, active or magnetic tumor-targeting abilities. And the employment of PLGA-based DDSs for remotely triggered cancer therapy were further discussed, including ultrasound-triggered, photo-triggered, magnetic field-triggered, and radiofrequency-triggered cancer therapy. Ultrasound-triggered cancer therapy involves high intensity focused ultrasound (HIFU) treatment, ultrasound-triggered chemotherapeutic release, and ultrasound-enhanced efficiency of gene transfection. Photo-triggered cancer therapy involves photodynamic therapy (PDT), photothermal therapy (PTT), and photo-triggered chemotherapeutic release. Additionally, we also discuss the strategies which endows PLGA-based DDSs with imaging properties. Numerous studies cited in our review demonstrate the great potential of PLGA-based DDSs as effective theranostic agent for cancer therapy and diagnosis.